I’ll take learning for 500 : - Yaman, Dan (Pfeiffer, 2006)
While there have been numerous books on using games for learning, there has never been one that focuses on the cultural phenomenon of game shows. This book illustrates the many different elements that are required to make a effective "game show" games—everything from writing effective questions, to changing pre-existing game show rules, to hosting, to creating new games.